Стохастичне планування експерименту в завданнях ймовірнісного комп’ютерного управління процесами регулювання координат в електрометалургії - Труфанов, І. Д.; Лютий, О. П.; Чумаков, К. І.; Жорняк, О. Е.; Никоненко, І. В.; Кащук, І. О. (Eastern-European Journal of Enterprise Technologies, 2009)
The dynamic functioning of computer stochastic system of imitating coordinates regulation of furnace electro technological complex on the basis of arch steel melting furnaces theoretical and mathematical research is carried out. Dispersive analysis of outer factors is made according «Dneprospecstal» factory complex, which acts on the basis of regulating action component, cluster and dynamic synthesis models.